2012
DOI: 10.1371/journal.pgen.1002515
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysiological Defects and Neuronal Gene Deregulation in Drosophila mir-124 Mutants

Abstract: miR-124 is conserved in sequence and neuronal expression across the animal kingdom and is predicted to have hundreds of mRNA targets. Diverse defects in neural development and function were reported from miR-124 antisense studies in vertebrates, but a nematode knockout of mir-124 surprisingly lacked detectable phenotypes. To provide genetic insight from Drosophila, we deleted its single mir-124 locus and found that it is dispensable for gross aspects of neural specification and differentiation. On the other ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
1
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 78 publications
3
44
1
1
Order By: Relevance
“…5A and Supplemental Fig. S6; see also Farh et al [2005]; Sun et al [2012]). Note that the P CT compensates for 3 ′ UTR overall conservation (binding sites located in highly conserved UTRs have to be even more conserved themselves to attain the same P CT than binding sites in poorly conserved UTRs).…”
Section: Titration Refines Mirna Expression Patternsmentioning
confidence: 92%
“…5A and Supplemental Fig. S6; see also Farh et al [2005]; Sun et al [2012]). Note that the P CT compensates for 3 ′ UTR overall conservation (binding sites located in highly conserved UTRs have to be even more conserved themselves to attain the same P CT than binding sites in poorly conserved UTRs).…”
Section: Titration Refines Mirna Expression Patternsmentioning
confidence: 92%
“…While most loss-of-function and overexpression studies in vertebrates supports miR-124 as a promoter of neuronal differentiation and an inhibitor of progenitor self-renewal (discussed further below), independent reports that studied miR-124 knockout in Drosophila showed that it is grossly dispensable for neuronal differentiation, but rather required for proliferation of neural stem cells [34-36]. Several possibilities could underlie the apparent divergence in the function of miR-124.…”
Section: Specific Micrornas and Their Roles In Neuronal Differentiatimentioning
confidence: 99%
“…Several possibilities could underlie the apparent divergence in the function of miR-124. Notably in flies miR-124 is expressed in proliferating neuroblasts, whereas in vertebrates, its expression starts when double-cortin positive neurons appear [34,35,37,38]. Similarly, in human embryonic stem cell to neuron differentiation system, miR-124 expression was largely restricted to differentiated neurons [39].…”
Section: Specific Micrornas and Their Roles In Neuronal Differentiatimentioning
confidence: 99%
“…Somewhat surprisingly, however, mutational inactivation in C. elegans (Miska et al 2007) and D. melanogaster (Weng and Cohen 2012;Sun et al 2012), which in contrast to mammals possess only one gene coding for miR-124, leaves homozygous mutants viable and without gross abnormalities. In Drosophila, a range of mutant phenotypes can be found, notably compromised of neuronal progenitor proliferation with a decreased number of Elav-positive cells per type I neuroblast-derived clone (Weng and Cohen 2012), and incomplete transition from neuroblast to neuronal gene expression signature (Sun et al 2012), but no complete failure of neuron generation.…”
Section: Distinct Sox Proteins Are Involved In Rostral and Caudal Gutmentioning
confidence: 99%
“…In Drosophila, a range of mutant phenotypes can be found, notably compromised of neuronal progenitor proliferation with a decreased number of Elav-positive cells per type I neuroblast-derived clone (Weng and Cohen 2012), and incomplete transition from neuroblast to neuronal gene expression signature (Sun et al 2012), but no complete failure of neuron generation. miR-9: a critical link to vertebrate proneural gene function Similar to miR-124, miR-9 is initially identified as a brainenriched microRNA (see Coolen et al 2013 for review).…”
Section: Distinct Sox Proteins Are Involved In Rostral and Caudal Gutmentioning
confidence: 99%